Proceedings of the 2009 Conference on Future Play on @ GDC Canada 2009
DOI: 10.1145/1639601.1639611
|View full text |Cite
|
Sign up to set email alerts
|

Game research, measuring gaming preferences

Abstract: The development and validation of tools and measurements for gaming experiences is an ongoing challenge for game studies researcher. This paper describes a questionnaire that collects information on fine-grained gaming preferences across genres. The data is analyzed quantitatively. Results obtained from this tool point out to what specific aspects of games are preferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 6 publications
1
14
1
Order By: Relevance
“…In the context of games and gaming, several attempts on predicting the effectiveness of the application of FFM showed inconsistent results [ 64 , 65 ]. In one study, personality traits have been related to preference for game genres [ 66 ]. A low predictive capability was found, which may be caused by a lack of evidence on whether the FFM is a valid method to measure personality in a game or not [ 67 , 68 ]; however, direct correlations between the FFM and gaming were researched and described by Vandenberghe [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the context of games and gaming, several attempts on predicting the effectiveness of the application of FFM showed inconsistent results [ 64 , 65 ]. In one study, personality traits have been related to preference for game genres [ 66 ]. A low predictive capability was found, which may be caused by a lack of evidence on whether the FFM is a valid method to measure personality in a game or not [ 67 , 68 ]; however, direct correlations between the FFM and gaming were researched and described by Vandenberghe [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar to traditional sports, video games have a substantial number of genres (types). Their unique mechanics attract different types of people, as shown by the relationship between personality traits and video games preferences ( Zammitto, 2010 ; Borders, 2012 ; Peever et al, 2012 ). As in typical sports, eSports can take the form of either individual or team-based competition.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this study showed that the gaming profile influences motivational outcomes both in traditional and game-based education. This finding, which can be accounted for because gaming preferences are a factor directly related to personality, as Zammitto suggests [83], opens up a new field of possibilities.…”
Section: Discussionmentioning
confidence: 85%